Β Blocker treatment and other prognostic variables in patients with clinical evidence of heart failure after acute myocardial infarction: evidence from the AIRE study. Issue 1 (1st January 1999) - Spargias, K S; Hall, A S; Greenwood, D C; Ball, S G
Abstract : Objectives: To examine clinical outcomes associated with optional β blockade in a population of patients with evidence of heart failure after myocardial infarction. Design and patients: Data from the acute infarction ramipril efficacy (AIRE) study were analysed retrospectively. At baseline 22.3% of the patients were receiving a β blocker. To minimise confounding, β blocker and diuretic treatments, presence of clinical signs of heart failure, left ventricular ejection fraction, and 16 other baseline clinical variables were simultaneously entered in a multivariate Cox regression model. In addition, the same analysis was repeated separately within a high and a low risk group of patients, as defined according to the need for diuretic treatment. Results: β Blocker treatment was an independent predictor of reduced risk of total mortality (hazard ratio 0.66, 95% confidence interval (CI) 0.48 to 0.90) and progression to severe heart failure (0.58, 95% CI 0.40 to 0.83) for the entire study population. There were similar findings in high risk patients requiring diuretics (0.59, 95% CI 0.40 to 0.86; and 0.58, 95% CI 0.38 to 0.89). Conclusions: β Blocker treatment is associated with improved outcomes in patients with clinical evidence of mild to moderate heart failure after myocardial infarction. Most importantly, high risk patients with persistent heart failure appear to benefit at least as much as lower risk patients with transient heart failure.